Examination of Mechanical Writing Skills of Primary School Students - Yasin Özcan; Volkan Sarıboğa; Sinem Güçlüer; Muhammet Baştuğ; Elife Nur Saydam (Sakarya University Journal of Education)
The foundations of writing, one of the four basic language skills, are laid in the primary school years and this skill is formally acquired during the first literacy teaching process in the 1st grade of primary school. Analyzing the writing skills of primary school students is essential for detecting weaknesses in their writing abilities, preventing potential writing difficulties in subsequent years, and designing intervention programs to enhance their writing competencies. In this context, this study aimed to examine the writing skills of primary school 1st through 4th grade students in terms of mechanics. The students’ notebook writings were assessed based on the following criteria: the size and shape of the letters, the alignment and order of the writing, the spacing between words and letters, the layout and neatness of the paper, the quantity and quality of the writing on the page and in the notebook, and the expression and meaningful coherence of the writing. The sample of the study, which was conducted with a descriptive survey using quantitative methods, consisted of a total of 807 primary school students studying in districts of different socioeconomic levels in Istanbul and the students’ writing notebooks. The “Writing Achievement Assessment Form,” which was prepared by the researchers and revised following the opinion of a classroom education specialist, was used as a data collection tool in the study. As a result of the study, it was determined that the writing skills of primary school students were at different levels in terms of mechanics. In addition, it was observed that the deficiencies in students’ mechanical writing skills were included in different criteria items. Based on the results obtained, the researchers have made suggestions to contribute to the field.